AN EVALUATION OF THE CREDIT RISK MANAGEMENT OF THE FINANCIAL INSTITUTIONS - Sangeetha, Dr.M. (The journal of contemporary issues in business and government, 2023)
Background/Objectives: CRM evolution is justified the idea on the implications of the financial industries where all of the information’s are properly impact. In order to the financial criteria is defined on this study as much as possible. Material and methods: Survey analysis is properly determined in the primary qualitative methods with the 55 responses. Significance of the study: The significance of the study on the evolution on the growth of a better data in the fundamental aspect based. Findings: The result findings symbolize the various knowledge of the CRM in the improvement of the financial sector. Conclusion: There is the improvement process in the CRM in the financial industries as much as possible. All of the impact is determined in the growth of this paper.